Anticoagulation-related intracranial extracerebral haemorrhage. Issue 7 (July 1989) - Mattle, H; Kohler, S; Huber, P; Rohner, M; Steinsiepe, K F
Abstract : From January 1981 to June 1986 116 patients with anticoagulation-related intracranial haemorrhage were referred to hospital. Seventy six of these haemorrhages were extracerebral, 69 were in the subdural and seven in the subarachnoid space. No epidural haemorrhages were identified. Compared with non-anticoagulation-related haematomas, the risk of haemorrhage was calculated to be increased fourfold in men and thirteenfold in women. An acute subdural haematoma, mostly due to contusion, was more frequently accompanied by an additional intracerebral haematoma than a chronic subdural haematoma. Trauma was a more important factor in acute subdural haematomas than in chronic. Almost half of the patients (48%) had a history of hypertension, more than a third (35%) had heart disease and about one fifth (18%) were diabetic. Headache was the most frequent initial symptom. Later decreased level of consciousness and focal neurological signs exceeded the frequency of headache. Three patients with subarachnoid haemorrhage and nine patients with acute subdural haematomas died, while those with chronic subdural haematomas all survived and had at the most mild, non-disabling sequelae. Myocardial infarction (22%), pulmonary embolism (20%), and arterial disease (20%) were the most frequent reasons for anticoagulant treatment. Critical review based on established criteria for anticoagulation treatment suggests there was no medical reason to treat a third of these patients. The single most useful measure that could be taken to reduce the risk of anticoagulation-induced intracranial haemorrhage would be to identify patients who are being unnecessarily treated and to discontinue anticoagulants.